2017
DOI: 10.1096/fj.201601244rr
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial microparticles prevent lipid‐induced endothelial damage via Akt/eNOS signaling and reduced oxidative stress

Abstract: Endothelial microparticles (EMPs) are endothelium-derived submicron vesicles that are released in response to diverse stimuli and are elevated in cardiovascular disease, which is correlated with risk factors. This study investigates the effect of EMPs on endothelial cell function and dysfunction in a model of free fatty acid (FFA) palmitate-induced oxidative stress. EMPs were generated from TNF-α-stimulated HUVECs and quantified by using flow cytometry. HUVECs were treated with and without palmitate in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…Furthermore, MVs play an important role in body fluids and tissues. Studies have shown that MVs can be derived from many types of cells, such as endothelial cells, erythrocytes, leucocytes, platelets and nerve cells, and in response to different stimuli, the release level of MVs in diseases is significantly higher than normal levels, such as the elevated level of endothelial microvesicles (EMVs) in cardiovascular disease, and hepatocyte from patients with hepatocellular carcinoma releases more MVs than normal hepatocytes . These phenomena indicate that MV release is correlated to the risk factors of cell exposure.…”
Section: Mvs and Its Active Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MVs play an important role in body fluids and tissues. Studies have shown that MVs can be derived from many types of cells, such as endothelial cells, erythrocytes, leucocytes, platelets and nerve cells, and in response to different stimuli, the release level of MVs in diseases is significantly higher than normal levels, such as the elevated level of endothelial microvesicles (EMVs) in cardiovascular disease, and hepatocyte from patients with hepatocellular carcinoma releases more MVs than normal hepatocytes . These phenomena indicate that MV release is correlated to the risk factors of cell exposure.…”
Section: Mvs and Its Active Moleculesmentioning
confidence: 99%
“…Microvesicles are spherical membranous vesicles encapsulated by a lipid molecular layer, and the cell spontaneously or, under certain conditions, the cell membrane phosphate ester serine valgus, which is redistributed to the outer side of the membrane in the bud and is released to the cell outside the subcellular component. 11 shown that MVs can be derived from many types of cells, such as endothelial cells, erythrocytes, leucocytes, platelets and nerve cells, 12 and in response to different stimuli, the release level of MVs in diseases is significantly higher than normal levels, such as the elevated level of endothelial microvesicles (EMVs) in cardiovascular disease, 13 and hepatocyte from patients with hepatocellular carcinoma releases more MVs than normal hepatocytes. 14 An interesting study revealed that the co-culture of normal bone marrow mesenchymal cell-derived MVs with multiple myeloma cells can reduce the viability, proliferation and migration of multiple myeloma cells, while MVs from multiple myeloma patients can enhance these biological effects.…”
Section: Characteristics Of Mvs Under Different Conditionsmentioning
confidence: 99%
“…In addition to their diagnostic potential, however, recent studies have shown a tremendous capacity for EVs to serve as therapeutic agents and restore tissue homeostasis [31]. Endothelial EVs can carry function endothelial nitric oxide synthase (eNOS), which works in an autocrine manner to restore homeostasis following fatty acid-induced oxidative stress [32]. In a similar manner, introduction of EVs obtained from cultured cells can prevent or reverse pathological remodeling in cardiovascular tissues.…”
Section: Extracellular Vesicles As Therapeutic Vehicles and Diagnostimentioning
confidence: 99%
“…Using a model of oxidative stress induced by free fatty acids, MV produced upon TNF stimulation of endothelial cells were shown to carry functional eNOS and to protect against oxidative stress by positively regulating eNOS/Akt signaling, which restored NO production, increased superoxide dismutase and catalase, and suppressed NADPH oxidase and ROS production. These data illustrate the important role of endothelial MV in the feedback loop of damage and repair during homeostasis, as well as in the protection against oxidative stress …”
Section: Production Of Ev By Endothelial Cellsmentioning
confidence: 59%